DOI: 10.24124/2022/59306
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care ultrasound education needs for nurse practitioners in primary care settings: An integrative review

Abstract: Point-of-care ultrasonography (POCUS) is the process of operating a compact ultrasound machine at a patient's location and immediately integrating the images generated into patient care. POCUS can help nurse practitioners (NPs) make more accurate diagnoses, facilitate safer procedures, and bridge health care access gaps in resource-limited settings such as primary care; however, it is widely agreed that POCUS is operator-dependent and that appropriate education is required to competently operate the device. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…While the literature demonstrating that RNs can safely operate POCUS continues to evolve, there are reports that nurses, physiotherapists, and respiratory therapists with appropriate training can safely operate POCUS with beneficial patient outcomes (See et al, 2016;Tulleken et al, 2019;Whittaker et al, 2007;Zisis et al, 2022). One hospital system in California has trained nurses to identify features of pulmonary edema, roughly estimate ejection fraction, and detect pathological features of cardiac physiology with POCUS (Lai & Paquin, 2020). Lastly, in a prospective observational study of fluid resuscitation among patients with sepsis, emergency RNs were found to have excellent inter-rater agreement with emergency physicians for all ultrasound scans, and these RNs were able to safely make adjustment to ongoing fluid resuscitation requirements (Selden et al, 2017).…”
Section: Can Emergency Nurses Be Certified To Operate Pocus?mentioning
confidence: 99%
“…While the literature demonstrating that RNs can safely operate POCUS continues to evolve, there are reports that nurses, physiotherapists, and respiratory therapists with appropriate training can safely operate POCUS with beneficial patient outcomes (See et al, 2016;Tulleken et al, 2019;Whittaker et al, 2007;Zisis et al, 2022). One hospital system in California has trained nurses to identify features of pulmonary edema, roughly estimate ejection fraction, and detect pathological features of cardiac physiology with POCUS (Lai & Paquin, 2020). Lastly, in a prospective observational study of fluid resuscitation among patients with sepsis, emergency RNs were found to have excellent inter-rater agreement with emergency physicians for all ultrasound scans, and these RNs were able to safely make adjustment to ongoing fluid resuscitation requirements (Selden et al, 2017).…”
Section: Can Emergency Nurses Be Certified To Operate Pocus?mentioning
confidence: 99%